(untitled) (Annals of Medical Research, 2021)
Aim: Recurrent nasopharyngeal carcinoma (NPC) after previous radiation therapy is a major problem. This study was conducted to determine the survival benefits and potential benefits of the effects of severe late toxicities by re-irradiation with fractionated stereotactic radiotherapy (FSRT).Material and Methods: 2009-2018, treatment outcomes were evaluated retrospectively in 26 patients with local recurrent NPC were cured applying FSRT with Cyberknife. Five patients had metastatic disease and one had second recurrence was excluded from the research, remaining 20 patients were analyzed. Median agewas 52 years (range,28-80 years), re-treatment T stagewas; 6 (30%) T2, 5 (25%) T3, 9 (45%) T4.Median time from initial RT to recurrence was 22 months (range,8-159 mo.). The median re-irradiation FSRT dose was 30Gy in 5 fractions.Results: Median follow-up was44 (22-179)months, the overall survival(OS) rate, local failure-free survival (LFFS ) and disease progression-free survival(DPFS) rate at 3 years were 89%,73% and 53%, respectively. All patients were evaluated for response after treatment; 9 (45%) had complete, 3 (15%) partial, 6 (%30) had no response.Univariate analysis demonstrated that; higher cumulative total radiotherapy dose, gross tumor volume and recurrent time interval were prognostic factors for LFFS. Recurrent time interval was also independent factor for DPFS and OS. The incidence of temporal lobe necrosis and trismus were 10% and 20%,respectively. One patient had grade 5 toxicity to treatment related bleeding.Conclusion: Tumor dose coverage is critical for treating recurrent NPC and treatment linked death rate was vascular in nature. Fractionated stereotactic radiotherapy is promising treatment modality for recurrent NPC.